PENGARUH MEDIA PEMBELAJARAN DIGITAL TERHADAP PENINGKATAN HASIL BELAJAR DAN KEMAMPUAN BERPIKIR KRITIS SEKOLAH DASAR - Fadhil Musyaffa, Irsyad; Ayu Az Zahra, Dellayla; Wardani, Sri; Widiarti, Nuni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Education in the digital era demands the integration of technology in the learning process. This article is a literature review on the use of technology-based learning media to improve learning outcomes and critical thinking skills of students in primary schools. It reviews journals that discuss different types of learning media, including mobile applications, interactive learning software, and e-learning platforms, and the problems that may be encountered in their implementation. Data were collected through a meta-analysis method based on electronic journal articles accessed through Google Scholar. The research data sources came from 20 national and international journal articles. The data obtained was then presented in a qualitative description. The researcher explores technology in learning while discussing challenges such as accessibility, infrastructure and teacher training. In addition, the article also discusses the importance of improving critical thinking skills through technology-based learning media, as well as methods that can be used to achieve this goal. Through comprehensive analyses, this article provides an insightful overview of the role of technology in enhancing learning at the primary level while discussing research directions and practices that need to be further explored.